Factors contributing to Malaysian youth participation in volunteerism: a functional approach to youth volunteers - Arif Shah, Jasmin; Hamzah, Siti Raba'ah; Suandi, Turiman; Ismail, Ismi Arif; Hamzah, Azimi (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Volunteerism is an important and increasingly popular mechanism for young people to bring about positive change in society by engaging themselves in global peace efforts and sustainable community development. The purpose of this study was to examine the factors contributing to Malaysian youth participation in volunteerism. Data were collected from the respondents using personally administered questionnaires. The participants (n=337) were youths 15 to 25 years of age (M age = 24.8). The findings indicated positive relationships between participation and helping power motivation, intention, and charity values. Helping power motivation and intention appeared to be more influential than other factors in the predictive analysis. It can be concluded that young people are key agents for social change, and are providing the energy, creative ideas and determination to drive innovation and reform. The paper can help policy makers reflect and focus their training efforts on the more practical aspects of day-to-day volunteering and the interpretation of leadership in youth development. As there is a paucity of literature in relation to youth and volunteerism, this study contributes to the knowledge base by identifying the reasons for youth engaging in volunteerism.